Evagrius Ponticus: Theology as a Way of Life - Kaminis, Ioannis (Forum Theologicum Sardicense, 2025)
Ioannis Kaminis, Evagrius Ponticus: Theology as a Way of Life. The paper explores the meaning and the different aspects of Evagrius’s Pon- ticus definition of Christianity. It presents his theological teaching, which is based on this definition and the eight tempting thoughts (λογισμοι) which must be confronted in order to reach the status of dispassion (ἀπαθεια). Actually the theological method of Evagrius Ponticus presents Christianity in a new light, not only as a religious teaching but as a way of life.